Patellar Tendon Ruptures after Total Knee Arthroplasty - Swartz, Gabrielle; Bonanni, Sean; Hameed, Daniel; Dubin, Jeremy A.; Bains, Sandeep S.; Patel, Deepak V.; Mont, Michael A.; Delanois, Ronald E.; Scuderi, Giles R. (The Journal of Knee Surgery, 2024)
Patellar tendon (PT) rupture following total knee arthroplasty (TKA) is a rare, but devastating complication. These injuries occur most frequently in the acute period following TKA due to trauma to the knee. PT ruptures that disrupt the extensor mechanism create a marked functional deficit, impacting every facet of daily life. In complete ruptures of the PT, repair or reconstruction is typically indicated; however, complication rates following intervention remain high. Operative intervention remains the mainstay of treatment, with only certain specific situations where nonoperative intervention is appropriate. Operative techniques are chosen based on the acuity, location of disruption, and status of the residual soft tissues. Treatment options include repair with or without augmentation or reconstruction. Augmentation does reduce the high risk of complications, bringing rates down from 63 to 25%. Augmentation options include autografts, allografts, synthetic grafts, or synthetic meshes. Despite advancements, outcomes are unpredictable and complications are common, highlighting the need for further research to improve treatment protocols. This article provides an overview of PT ruptures following TKA, the various treatment options, and the recommendations of the M.M., R.D., G.S. for each common type of PT injury encountered.
Keywords: total knee arthroplasty; complications; management